Theory of vortex sound - Howe, M. S. (Cambridge texts in applied mathematics., 2003)
The book is an introduction to theory of sound generation by fluid flow, specially written for a one semester course at advanced undergraduate or graduate level. Problems are provided at the end of each chapter, many of which can be used for extended student projects. A whole chapter is devoted to worked examples.